(untitled) (Indian Journal of Animal Production and Management, 2024)
A three months study was conducted on 18 Nellore lambs to evaluate the effect of incorporating different levels of Moringa oleifera leaf meal (MOLM) on haematological parameters. Nellore lambs in similar age and uniform conformation were allocated into three groups (T0, T1and T2) with 6 lambs per treatment using completely randomized block design. The lambs in T0, T1and T2 groups were offered concentrate feed incorporated with MOLM at 0, 15 and 30% levels, respectively. Blood samples were collected at the start and end of the study. Haematological study showed no significant changes except haematocrit which was significantly higher in control group than MOLM supplemented group. The results also revealed that all erythrocytes and leucocytes indices were within the normal physiological range.